Réponses

2014-04-21T18:32:35+02:00
A. x/3 = x/4 - 6/5
X/3-X/4 = -6/5
4/12x-3/12x = -6/5
1/12x = -6/5
x = -6/5 *12
x = -6*12 /5
x = - 72/5

b. 5x/8 - 3/10 = 7x / 40 
5/8x -7/40x = 3/10
25/40x -7/40x =3/10
18/40 x =3/10
x =3/10 *40/18
x = 120/180
x =12/18
x = 2/3

c. 2x/7 + 3/14 = x/7 - 1/14
2/7x -1/7x = -1/14 -3/14
1/7x =-4/14
1/7x = -2/7
x = -2/7 x 7
x =-14/7
x = -2

d. 2/5 x - 1/9 = 3/9 x + 4/5
2/5x -3/9x = 4/5 +1/9
18/45x -15/45 x = 36/45 +5/45
3/45x = 41/45
1/15x =41/45
x = 41/45 *15
x = 41/3